Method for coating active materials using electrostatic spinning technology, coated active materials and applications

The active material is coated through electrospinning technology, which defines the relationship between the thickness and capacity of the cladding layer, solves the problem that the relationship between the thickness of the cladding layer and the capacity of the active material in the prior art has not been studied, and realizes active materials with high capacity and excellent circulation performance.

CN119252905BActive Publication Date: 2025-03-04TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411764878.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The prior art has failed to effectively study the relationship between the thickness of the coating layer and the capacity of the active material, resulting in insufficient capacity and circulation performance of the active material after coating.

Method used

The active material is coated by electrospinning technology, and the relationship between the first discharge specific capacity of the coated active material and the thickness of the cladding layer is defined, and the appropriate cladding layer thickness is selected to improve the capacity and cycling performance of the active material.

Benefits of technology

The coated active material has high actual first-time discharge specific capacity and exhibits excellent cycling and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252905B_ABST
    Figure CN119252905B_ABST
Patent Text Reader

Abstract

The present invention provides a method for coating an active material using electrospinning technology, a coated active material and an application. The coated active material comprises an active material core and a coating layer coated on the surface of the active material core; the coated active material satisfies the following conditions: when 0nm<d≤40nm, C estimated value=C 0 +4d‑0.15d 2 +0.0016d 3 ; When d>40nm, C estimated value = C 1 / (d‑40) 0.007 ; Wherein, C estimated value is the estimated value of the first discharge specific capacity of the coated active material, in units of mAh / g; C 0 The value range is 90-190; C 1 The value range of is 110-210; d is the thickness of the coating layer, in nm. Through the two relationship equations defined in the present invention, the relationship between the estimated first discharge specific capacity of the active material after coating and the thickness of the coating layer can be known, so that the appropriate coating layer thickness can be selected according to the first discharge specific capacity requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a method for coating active materials using electrostatic spinning technology, the coated active materials and applications. Background Art

[0002] The development of new energy vehicles has also led to the rapid expansion of the battery industry, especially the continued rapid development of the secondary battery industry, such as lithium secondary batteries. With the increasing demand for new energy vehicles, the requirements for the capacity and other performance of secondary batteries are getting higher and higher, so there is an urgent need to increase the capacity of electrode active materials. Currently, one of the commonly used methods to increase capacity is coating modification, which is to coat a layer of material on the surface of the active material.

[0003] During coating modification, the thickness of the coating layer has an important influence on the capacity of the active material after coating, but there is currently no research on the relationship between the thickness of the coating layer and the capacity of the active material after coating. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for coating active materials using electrostatic spinning technology, coated active materials and applications. The present invention defines the relationship between the first discharge specific capacity of the coated active material and the thickness of the coating layer. Through the two relationship formulas, the estimated first discharge specific capacity can be inferred according to the thickness of the coating layer, so that the appropriate coating layer thickness can be selected, so that the prepared coated active material has a high actual first discharge specific capacity and exhibits excellent cycle performance and safety performance.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a coated active material, wherein the coated active material comprises an active material core and a coating layer coated on the surface of the active material core.

[0007] The coated active material meets the following conditions:

[0008] When 0nm<d≤40nm, estimated value of C = C0+4d-0.15d 2 +0.0016d 3 .

[0009] When d>40nm, C estimated value = C1 / (d-40) 0.007 .

[0010] The estimated C value is the estimated first discharge specific capacity of the coated active material, in units of mAh / g.

[0011] The value range of C0 is 90-190, for example, it can be 90, 100, 110, 115, 118, 120, 130, 135, 140, 145, 150, 160, 170, 180, 188 or 190, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0012] The value range of C1 is 110-210, for example, it can be 110, 120, 130, 135, 137, 140, 150, 155, 160, 165, 170, 180, 190, 200 or 210, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] d is the thickness of the coating layer, in nm.

[0014] It should be noted that in the two equations provided by the present invention, the values ​​on both sides of the equal sign are equal, which means that the equation is established. In the two equations of the present invention related to the estimated value of C, the value of C0 or C1 depends on the material type of the active material core.

[0015] The present invention defines a relationship between an estimated value of the first discharge specific capacity of the coated active material and the coating layer thickness. Through the two relationship formulas, the estimated first discharge specific capacity can be inferred according to the coating layer thickness, so that a suitable coating layer thickness can be selected, so that the prepared coated active material has a high actual first discharge specific capacity and exhibits excellent cycle performance and safety performance.

[0016] Preferably, the active material core comprises a positive electrode active core or a negative electrode active core.

[0017] In the present invention, the material of the positive electrode active core includes a lithium battery positive electrode active material or a sodium battery positive electrode active material, and the lithium battery positive electrode active material includes but is not limited to lithium iron phosphate, lithium manganese oxide, lithium titanate, lithium cobalt oxide or lithium nickel cobalt manganese oxide, and the lithium nickel cobalt manganese oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2 or LiNi 0.5 Co 0.2 Mn 0.3 O2, etc.; the sodium positive electrode active material includes but is not limited to transition metal layered oxides or polyanion compounds, etc.

[0018] Exemplarily, the method for preparing the lithium battery positive electrode active material includes:

[0019] The precursor, lithium salt and additive are mixed and calcined to obtain the lithium battery positive electrode active material; wherein the precursor includes Co x Mn y X z O4 (x+y+z=3) and / or Ni x Co y Mn z X 1-x-y-z (OH)2 (x+y+z≤1), wherein X includes at least one of W, Al, La, Zr, Ti, Sr, Y, Sb, Nb or Ta elements; the lithium salt includes lithium carbonate and lithium hydroxide; the additive includes metal elements such as Al, Zr, Ti, La, Mo, Nb and / or non-metal elements such as B, P, Si and the like.

[0020] In the present invention, the material of the negative electrode active core includes carbon materials or non-carbon materials, the carbon materials include but are not limited to graphite, amorphous carbon or carbon nanotubes, etc., and the non-carbon materials include but are not limited to silicon-based materials, metallic lithium or titanium-based materials, etc.

[0021] For example, the C0 and C1 values ​​corresponding to the positive electrode active materials of lithium batteries are as follows: C0 for lithium cobalt oxide is 150 and C1 is 170; C0 for lithium manganese oxide is 90 and C1 is 110; C0 for lithium iron phosphate is 115 and C1 is 135; C0 for lithium titanate is 118 and C1 is 137; 0.8 Co 0.1 Mn 0.1 The C0 corresponding to O2 is 188, and the C1 is 210; LiNi 0.6 Co 0.2 Mn 0.2 The C0 corresponding to O2 is 145, and the C1 is 165; LiNi 0.5 Co 0.2 Mn 0.3 The C0 corresponding to O2 is 135, and the C1 is 155.

[0022] Preferably, the first discharge capacity test value of the coated active material is recorded as the C test value, and the absolute value of the difference between the C estimated value and the C test value is ≤5 mAh / g, for example, it can be 5 mAh / g, 4 mAh / g, 3 mAh / g, 2 mAh / g, 1 mAh / g or 0.5 mAh / g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] It should be noted that the C test value is the actual first discharge specific capacity of the coated active material obtained by testing means. The unit of the C test value is mAh / g.

[0024] In the present invention, the error between the estimated value of the first discharge specific capacity calculated by the two relationship expressions and the actually measured test value of the first discharge specific capacity is relatively small.

[0025] Preferably, the thickness of the coating layer is 2-100 nm, for example, it can be 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 65 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In a second aspect, the present invention provides a method for coating an active material using electrospinning technology, the method comprising:

[0027] (1) The coating agent, polymer and solvent are mixed to obtain a dispersion.

[0028] (2) Using the dispersion as the spinning solution and placing the active material in a flowing state, electrospinning is performed to form a coating precursor layer on the surface of the active material, followed by sintering to obtain the coated active material described in the first aspect.

[0029] It should be noted that the coating method using electrospinning technology of the present invention is applicable to both positive electrode active materials and negative electrode active materials. The coating precursor layer is composed of spun fibers, and the morphology of the spun fibers includes but is not limited to mesoporous nanotubes, rods or fibers.

[0030] The present invention provides a method for coating active materials using electrostatic spinning technology. During the electrostatic spinning process, since the active material is in a flowing state, a thin and uniform coating precursor layer can be formed on the surface of the active material, and a thin and uniform coating layer is formed after sintering. On the one hand, the thin coating layer can greatly reduce the interface impedance and increase the electron transmission rate; on the other hand, the coating layer can effectively isolate the direct contact between the electrolyte and the active material, reduce the side reaction with the electrolyte, and improve the stability of the active material. Under the combined effect of the above conditions, not only can the consistency, capacity performance, cycle performance, rate performance and storage performance of the battery be improved, but also the thermal stability and cycle stability of the battery can be effectively improved.

[0031] The present invention can completely remove the solvent and the polymer through the sintering process, and can make the coating agent and the active material fully integrated. In addition, the method provided by the present invention has simple process and low cost.

[0032] The coated active material prepared by the method of the present invention has a coating layer thickness and an initial discharge specific capacity that satisfy the relationship provided in the first aspect.

[0033] Preferably, the coating element in the coating agent includes at least one of W, Al, La, Zr, Ti, N, B, Si, P, Sr, Y, Nb, Mo or Ce. Among them, W, Al, La, Zr, Ti, Sr, Y, Nb, Mo and Ce are metal elements, and N, B, Si and P are non-metal elements.

[0034] Preferably, the coating agent is an organic or inorganic substance containing a coating element.

[0035] In the present invention, the polymer and the coating agent are used in combination, the water-soluble polymer is used in combination with an inorganic coating agent containing a coating element, such as an acid, a salt, etc.; the water-insoluble polymer is used in combination with an organic coating agent containing a coating element.

[0036] Preferably, based on the total mass of the dispersion as 100%, the mass fraction of the coating element in the coating agent is 0.1-70%, for example, it can be 0.1%, 0.5%, 1%, 2%, 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the polymer includes at least one of polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polystyrene (PS), polyimide (PI), polyvinylidene fluoride (PVDF), polymethacrylate (PMMA) or polyvinyl chloride (PVC).

[0038] In the present invention, polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol are water-soluble polymers, and polyacrylonitrile, polystyrene, polyimide, polyvinylidene fluoride, polymethacrylate and polyvinyl chloride are water-insoluble polymers.

[0039] Preferably, based on the total mass of the dispersion as 100%, the mass fraction of the polymer is 5-70%, for example, 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 10-40%.

[0040] In the present invention, the concentration and molecular weight of the polymer have a great relationship with the viscosity of the dispersion and are important factors in determining whether long and continuous fibers can be obtained. Therefore, it is necessary to select a suitable polymer and dosage.

[0041] Preferably, the solvent includes a first solvent and a second solvent.

[0042] Preferably, the first solvent and the second solvent independently include at least one of water, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N-methyl-2-pyrrolidone (NMP) or ethanol.

[0043] In the present invention, "independently" means that the types of the first solvent and the second solvent are selected without interfering with each other. Among them, water is used to dissolve water-soluble materials, and N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and ethanol are used to dissolve water-insoluble materials. According to the solubility properties of the coating agent and the polymer, the appropriate solvent type is selected.

[0044] Preferably, the first solvent and the second solvent are of the same type.

[0045] Preferably, the mixing in step (1) is step-by-step mixing, and the step-by-step mixing includes the following steps:

[0046] (i) The polymer and the first solvent are mixed for the first time to obtain a spinning solution A; and the coating agent and the second solvent are mixed for the second time to obtain a spinning solution B.

[0047] (ii) The spinning solution A and the spinning solution B are mixed for the third time to obtain the dispersion.

[0048] It should be noted that in step (i), the steps of preparing spinning solution A and preparing spinning solution B are carried out in no particular order.

[0049] In the present invention, step-by-step mixing can obtain a more uniformly dispersed dispersion, which is beneficial for making the coating layer more uniform and for promoting the performance.

[0050] Preferably, the temperature of the second mixing is 50-150°C, for example, it can be 50°C, 60°C, 80°C, 100°C, 110°C, 130°C or 150°C, etc.; the time is 1-48h, for example, it can be 1h, 2h, 5h, 10h, 15h, 20h, 30h, 40h or 48h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the first mixing, the second mixing and the third mixing include at least one of magnetic stirring, ultrasonic dispersion or mechanical stirring.

[0052] Preferably, in step (2), the active material is placed in a flowing state by air flow.

[0053] Preferably, the air pressure of the airflow is 0.01-2.00 MPa, for example, it can be 0.01 MPa, 0.05 MPa, 0.08 MPa, 1.00 MPa, 1.00 MPa, 1.20 MPa, 1.50 MPa or 2.00 MPa, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 0.05-1.20 MPa.

[0054] Preferably, the temperature of the air flow is 20-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the gas in the airflow is a dry gas, and the dew point of the dry gas is ≤-10°C, for example, it can be -10°C, -15°C, -20°C or -25°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In the present invention, dry gas is used to provide the gas flow in order to reduce the reaction between the active material (such as the positive electrode material) and the moisture in the air, because the generated byproducts will lead to an increase in the interface impedance.

[0057] Preferably, in step (2), an electrospinning device is used to carry out the electrospinning; the electrospinning device comprises a spinning chamber; a liquid supply assembly and a receiving assembly are arranged in the spinning chamber, the liquid supply assembly comprises a propeller, a syringe for containing spinning liquid and an injection needle connected to the syringe, the propeller is used to control the propulsion speed of the syringe, and the injection needle is arranged opposite to the receiving assembly; the injection needle and the receiving assembly are externally connected to a high-voltage power supply; a breathable cap is arranged on the top of the spinning chamber; an air inlet is arranged at the bottom of the spinning chamber, which is used to introduce air flow into the spinning chamber so that the active material flows in the area between the injection needle and the receiving assembly.

[0058] Preferably, a gas pipeline is provided below the spinning chamber, and a gas outlet of the gas pipeline is connected to a gas inlet of the spinning chamber.

[0059] Preferably, the electrospinning process comprises the following steps:

[0060] 1) Transfer the spinning solution into a syringe and install the injection needle, and set the advancement speed of the syringe so that the spinning solution in the syringe can be ejected at a constant rate.

[0061] 2) Place the active material in the spinning chamber where it is required, and introduce air flow through the air inlet to make the active material flow evenly up and down.

[0062] 3) Turn on the high-voltage power supply, apply voltage to one side of the injection needle and the other side of the receiving component, and start electrospinning. The solution ejected from the injection needle forms spinning fibers under the action of high voltage. After a certain period of time, a uniform coating precursor layer is formed on the surface of the flowing active material.

[0063] Preferably, during the electrospinning process, the pressure in the spinning chamber is 0.01-2.00 MPa, for example, it can be 0.01 MPa, 0.05 MPa, 0.08 MPa, 1.00 MPa, 1.00 MPa, 1.50 MPa or 2.00 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] Preferably, during the electrospinning process, the voltage of the high voltage power supply is 15-35 kV, for example, 15 kV, 20 kV, 25 kV, 30 kV or 35 kV, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] Preferably, during the electrospinning process, the distance between the injection needle and the receiving component is 10-30 cm, for example, it can be 10 cm, 12 cm, 15 cm, 20 cm, 25 cm or 30 cm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] Preferably, during the electrospinning process, the propulsion speed of the syringe is 0.01-3.00 mL / h, for example, it can be 0.01 mL / h, 0.02 mL / h, 0.05 mL / h, 0.1 mL / h, 0.15 mL / h, 0.5 mL / h, 1 mL / h, 1.5 mL / h, 2 mL / h, 2.5 mL / h or 3 mL / h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] Preferably, the electrospinning time is 1-600 min, for example, it can be 1 min, 2 min, 5 min, 10 min, 20 min, 50 min, 100 min, 200 min, 300 min, 400 min, 500 min or 600 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In the present invention, the thickness of the coating layer can be controlled by regulating the viscosity of the spinning solution and the electrospinning time.

[0069] Preferably, the sintering temperature in step (2) is 200-500°C, for example, it can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C; the sintering time is 2-10h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0070] Preferably, the sintering atmosphere includes an oxygen atmosphere or an argon atmosphere.

[0071] In a third aspect, the present invention provides a secondary battery, wherein the electrode of the secondary battery comprises the coated active material described in the first aspect, or the coated active material prepared by the method described in the second aspect.

[0072] The secondary battery includes, but is not limited to, a lithium secondary battery or a sodium secondary battery.

[0073] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] (1) The present invention defines a relationship between an estimated value of the first discharge specific capacity of the coated active material and the coating layer thickness. Through the two relationship equations, the estimated first discharge specific capacity can be inferred according to the coating layer thickness, so that a suitable coating layer thickness can be selected, so that the prepared coated active material has a high actual first discharge specific capacity and exhibits excellent cycle performance and safety performance.

[0076] (2) The present invention provides a method for coating active materials using electrospinning technology. During the electrospinning process, since the active material is in a flowing state, a thin and uniform coating precursor layer can be formed on the surface of the active material, and a thin and uniform coating layer is formed after sintering. On the one hand, the thin coating layer can greatly reduce the interface impedance and increase the electron transmission rate; on the other hand, the coating layer can effectively isolate the direct contact between the electrolyte and the active material, reduce the side reaction with the electrolyte, and improve the stability of the active material. Under the combined effect of the above conditions, not only can the consistency, capacity performance, cycle performance, rate performance and storage performance of the battery be improved, but also the thermal stability and cycle stability of the battery can be effectively improved.

[0077] (3) In the method provided by the present invention, the solvent and the polymer can be completely removed through the sintering process, and the coating agent and the active material can be fully integrated.

[0078] (4) The method provided by the present invention is simple in process and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 The figure is a schematic diagram of the structure of an electrospinning device provided in one embodiment of the present invention.

[0080] Figure 2 This is the relationship curve between the coating layer thickness of the active material after coating and the first discharge specific capacity.

[0081] Figure 3 The DSC test curves of Example 1, Comparative Example 1 and Comparative Example 2 in the present invention are shown.

[0082] Figure 4 These are the cycle curves of Example 1, Comparative Example 1 and Comparative Example 2 in the present invention.

[0083] Among them, 1-gas pipeline; 2-breathable cap; 3-syringe; 4-receiving plate; 5-gas inlet. DETAILED DESCRIPTION

[0084] It should be understood that in the description of the present invention, the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0085] It should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "disposed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.

[0086] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0087] In one embodiment, the present invention provides an electrospinning device, the structural schematic diagram of which is as follows Figure 1 As shown, the electrospinning equipment includes a spinning chamber; a liquid supply assembly and a receiving plate 4 are arranged in the spinning chamber, the liquid supply assembly includes a propeller, a syringe 3 for containing spinning liquid and an injection needle connected to the syringe 3, the propeller is used to control the propulsion speed of the syringe 3, and the injection needle is arranged opposite to the receiving plate 4; the injection needle and the receiving plate 4 are externally connected to a high-voltage power supply; an air inlet 5 is arranged at the bottom of the spinning chamber for introducing air flow into the spinning chamber so that the active material flows in the area between the injection needle and the receiving plate 4; a breathable cap 2 is arranged on the top of the spinning chamber; a gas pipeline 1 is arranged below the spinning chamber, and the gas outlet of the gas pipeline 1 is connected to the air inlet 5 of the spinning chamber.

[0088] Example 1

[0089] This embodiment provides a method for coating an active material using electrospinning technology, the method comprising:

[0090] (1) 10 g of polyacrylonitrile (PAN) was added to 80 mL of N,N-dimethylformamide (DMF), and the mixture was stirred at 60°C for 12 h to obtain a spinning solution A; 2.358 g of LiNbO3 was added to 20 mL of DMF, and the mixture was stirred at 60°C for 12 h to obtain a spinning solution B; the spinning solution A and the spinning solution B were mixed at a volume ratio of 6:4, and the mixture was stirred at 50°C for 12 h to obtain a viscous, uniform and transparent light yellow dispersion;

[0091] (2) Weigh the precursor Ni 0.8 Co 0.1 Mn 0.1 100 g of (OH)2, 47.35 g of lithium hydroxide monohydrate and 0.600 g of zirconium oxide were mixed and sintered at 800 °C for 12 h in an oxygen atmosphere. After sintering, the mixture was cooled to room temperature, taken out and crushed and sieved to obtain the ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 (LNCM-811).

[0092] (3) The ternary cathode material LNCM-811 is placed in the spinning chamber of the electrospinning equipment, and a dry gas is introduced through the air inlet to form an air flow so that the ternary cathode material LNCM-811 flows evenly up and down, the dew point of the dry gas is -30°C, the air pressure of the air flow is 0.20 MPa, the temperature of the air flow is 25°C, and the pressure in the spinning chamber is 0.19 MPa; the dispersion is used as the spinning solution, and it is loaded into a 10 mL syringe, the voltage of the high-voltage power supply is set to 20 kV, the propulsion speed is 0.6 mL / h, the distance between the injection needle and the receiving plate is 15 cm, and the spinning time is 120 min; the high-voltage power supply is turned on, and electrospinning is performed to form a uniform coating precursor layer on the surface of the flowing ternary cathode material LNCM-811.

[0093] (4) After the electrospinning is completed, the power of the equipment is turned off, and the material obtained in step (3) is taken out and sintered at 300°C for 5 hours in an oxygen atmosphere. After the sintering is completed, it is cooled to room temperature and taken out and sieved to obtain the coated active material, wherein the thickness of the coating layer is about 15 nm.

[0094] Example 2

[0095] This embodiment provides a method for coating an active material using electrospinning technology, the method comprising:

[0096] (1) preparing a PVA aqueous solution with a mass concentration of 20%, and stirring it magnetically at 95° C. until it is completely dissolved to obtain a spinning solution A; preparing an AlCl3 aqueous solution with a mass concentration of 10%, and stirring it magnetically at 25° C. until it is completely dissolved to obtain a spinning solution B; mixing the spinning solution A and the spinning solution B in a volume ratio of 6:4, and stirring at 50° C. for 12 hours to obtain a dispersion;

[0097] (2) Weigh 100 g of cobalt tetroxide and 47.35 g of lithium carbonate, mix them, sinter them at 950° C. for 20 h in an oxygen atmosphere, cool them to room temperature after sintering, take them out, crush them and sieve them to obtain a lithium cobalt oxide positive electrode material.

[0098] (3) Placing the lithium cobalt oxide positive electrode material in the spinning chamber of the electrospinning equipment, introducing dry gas through the air inlet to form an air flow so that the lithium cobalt oxide positive electrode material flows evenly up and down, the dew point of the dry gas is -30°C, the air pressure of the air flow is 0.80 MPa, the temperature of the air flow is 25°C, and the pressure in the spinning chamber is 0.79 MPa; using the dispersion as the spinning liquid, loading it into a 10 mL syringe, setting the voltage of the high-voltage power supply to 25 kV, the propulsion speed to 1 mL / h, the distance between the injection needle and the receiving plate to 20 cm, and the spinning time to 180 min; turning on the high-voltage power supply, performing electrospinning, and forming a uniform coating precursor layer on the surface of the flowing lithium cobalt oxide positive electrode material.

[0099] (4) After the electrospinning is completed, the power of the equipment is turned off, and the material obtained in step (3) is taken out and sintered at 280°C for 8 hours in an oxygen atmosphere. After the sintering is completed, it is cooled to room temperature and taken out and sieved to obtain the coated active material, wherein the thickness of the coating layer is about 5 nm.

[0100] Example 3

[0101] This embodiment provides a method for coating an active material using electrospinning technology, the method comprising:

[0102] (1) Add polyvinylidene fluoride (PVDF) to NMP to prepare 80 mL of a PVDF solution with a mass concentration of 50%, and then stir at 35°C until it is completely dissolved to obtain a spinning solution A; add 1.8 g of ammonium tungstate to 10 mL of NMP, stir magnetically at 25°C until it is completely dissolved, and then add 2.5 g of strontium carbonate and continue stirring until it is completely dissolved to obtain a spinning solution B; mix the spinning solution A and the spinning solution B in a volume ratio of 4:6, and stir until they are completely mixed to obtain a dispersion;

[0103] (2) Weigh 100 g of manganese tetraoxide and 49.35 g of lithium carbonate, mix them, sinter them at 860° C. for 15 h in an oxygen atmosphere, cool them to room temperature after sintering, take them out, crush them and sieve them to obtain a lithium manganate positive electrode material.

[0104] (3) The lithium manganese oxide positive electrode material is placed in the spinning chamber of the electrospinning equipment, and a dry gas is introduced through the air inlet to form an air flow so that the lithium manganese oxide positive electrode material flows evenly up and down, wherein the dew point of the dry gas is -30°C, the air pressure of the air flow is 1.20 MPa, the temperature of the air flow is 25°C, and the pressure in the spinning chamber is 1.19 MPa; the dispersion is used as the spinning liquid, and it is loaded into a 10 mL syringe, the voltage of the high-voltage power supply is set to 30 kV, the propulsion speed is 1.2 mL / h, the distance between the injection needle and the receiving plate is 30 cm, and the spinning time is 200 min; the high-voltage power supply is turned on, and electrospinning is performed to form a uniform coating precursor layer on the surface of the flowing lithium manganese oxide positive electrode material.

[0105] (4) After the electrospinning is completed, the power of the equipment is turned off, and the material obtained in step (3) is taken out and sintered at 350°C for 5 hours in an oxygen atmosphere. After the sintering is completed, it is cooled to room temperature and taken out and sieved to obtain the coated active material, wherein the thickness of the coating layer is about 11 nm.

[0106] Example 4

[0107] This embodiment provides a method for coating an active material using electrospinning technology, the method comprising:

[0108] (1) preparing a PVA aqueous solution with a mass concentration of 30%, and magnetically stirring it at 95° C. until it is completely dissolved to obtain a spinning solution A; preparing a H3BO3 aqueous solution with a mass concentration of 10%, and magnetically stirring it at 25° C. until it is completely dissolved to obtain a spinning solution B; mixing the spinning solution A and the spinning solution B in a volume ratio of 6:4 to obtain 100 mL of a mixed solution, and stirring it at 50° C. until it is completely mixed to obtain a dispersion;

[0109] (2) The FePO4 precursor and lithium carbonate were mixed in a molar ratio of 1:0.5, and ground in a mortar for 1 hour to achieve uniform mixing of the materials to obtain a mixture. The mixture was placed in an argon atmosphere and sintered at 680°C for 8 hours. After sintering, it was cooled to room temperature, taken out, crushed and sieved to obtain a lithium iron phosphate positive electrode material.

[0110] (3) Placing the lithium iron phosphate positive electrode material in the spinning chamber of the electrospinning equipment, introducing dry gas through the air inlet to form an air flow so that the lithium iron phosphate positive electrode material flows evenly up and down, the dew point of the dry gas is -30°C, the air pressure of the air flow is 1.80 MPa, the temperature of the air flow is 25°C, and the pressure in the spinning chamber is 1.79 MPa; using the dispersion as the spinning solution, loading it into a 10 mL syringe, setting the voltage of the high-voltage power supply to 25 kV, the propulsion speed to 1.0 mL / h, the distance between the injection needle and the receiving plate to 20 cm, and the spinning time to 180 min; turning on the high-voltage power supply, performing electrospinning, and forming a uniform coating precursor layer on the surface of the flowing lithium iron phosphate positive electrode material.

[0111] (4) After the electrospinning is completed, the power of the equipment is turned off, and the material obtained in step (3) is taken out and sintered at 280°C for 8 hours in an oxygen atmosphere. After the sintering is completed, it is cooled to room temperature and sieved to obtain the coated active material, wherein the thickness of the coating layer is about 10 nm.

[0112] Example 5

[0113] The difference between this embodiment and embodiment 1 is that the air pressure of the airflow in step (3) is 0.005 MPa.

[0114] The remaining preparation methods and parameters were consistent with those in Example 1, and the thickness of the final coating layer was about 28 nm.

[0115] Example 6

[0116] The difference between this embodiment and embodiment 1 is that the air pressure of the airflow in step (3) is 2.0 MPa.

[0117] The remaining preparation methods and parameters were consistent with those in Example 1, and the thickness of the final coating layer was about 8 nm.

[0118] Example 7

[0119] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (4) is 150°C.

[0120] The remaining preparation methods and parameters were consistent with those in Example 1, and the thickness of the final coating layer was about 33 nm.

[0121] Example 8

[0122] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (4) is 550°C.

[0123] The remaining preparation methods and parameters were consistent with those in Example 1, and the thickness of the final coating layer was about 6 nm.

[0124] Example 9

[0125] The difference between this embodiment and embodiment 1 is that the spinning time is adjusted to 500 min.

[0126] The rest of the preparation methods and parameters were the same as those in Example 1.

[0127] In the coated active material finally obtained in this embodiment, the thickness of the coating layer is about 50 nm.

[0128] Comparative Example 1

[0129] The difference between this comparative example and Example 1 is that step (1), step (3) and step (4) are not performed, and the ternary positive electrode material LNCM-811 prepared in step (2) is used as the active material.

[0130] The rest of the preparation methods and parameters were the same as those in Example 1.

[0131] Comparative Example 2

[0132] The difference between this comparative example and Example 1 is that step (1), step (3) and step (4) are not performed, and the ternary positive electrode material LNCM-811 obtained in step (2) is subjected to a fire coating of LiNbO3. The coating conditions are sintering at 300°C for 5 h in an oxygen atmosphere, cooling to room temperature, taking out and sieving to obtain a coated active material, wherein the thickness of the coating layer is about 2 nm.

[0133] The rest of the preparation methods and parameters were the same as those in Example 1.

[0134] Comparative Example 3

[0135] The difference between this comparative example and Example 2 is that step (1), step (3) and step (4) are not performed, and the lithium cobalt oxide positive electrode material prepared in step (2) is used as the active material.

[0136] The rest of the preparation methods and parameters were the same as those in Example 2.

[0137] Comparative Example 4

[0138] The difference between this comparative example and Example 3 is that step (1), step (3) and step (4) are not performed, and the lithium manganese oxide positive electrode material prepared in step (2) is used as the active material.

[0139] The rest of the preparation methods and parameters were the same as those in Example 3.

[0140] Comparative Example 5

[0141] The difference between this comparative example and Example 4 is that step (1), step (3) and step (4) are not performed, and the lithium iron phosphate positive electrode material prepared in step (2) is used as the active material.

[0142] The rest of the preparation methods and parameters were the same as those in Example 4.

[0143] Performance Testing

[0144] (1) Test on the relationship between coating thickness and initial discharge specific capacity:

[0145] Based on the preparation method of Example 1, the thickness of the coating layer is regulated by adjusting the spinning time to obtain coated active materials with different coating layer thicknesses, and then the prepared materials are used as positive electrode active materials to prepare button batteries respectively. The specific steps include: weighing the positive electrode active material, acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3, mixing them evenly, adding NMP and stirring for 20 minutes to form a viscous slurry, and evenly coating it on an aluminum foil, and then baking it in a vacuum oven at 80°C, pressing it into sheets, cutting a positive electrode sheet with a diameter of 14 mm, using a pure lithium sheet with a diameter of 16 mm as a negative electrode sheet, using a mixed solution of diethyl carbonate (DEC) / ethylene carbonate (EC) with a volume ratio of 1:1 with 1 mol / L LiPF6 as an electrolyte, and using a polypropylene microporous membrane as a diaphragm, and assembling them into a button CR2032 battery in a glove box filled with argon.

[0146] Test conditions: In the voltage range of 2.5-4.25V, the button battery is charged at 0.2C constant current and constant voltage, and then discharged at 0.2C constant current to obtain the first discharge specific capacity.

[0147] The coating thickness of each coated active material and the corresponding first discharge specific capacity measured are statistically analyzed in Figure 2The relationship curve between the coating thickness and the first discharge specific capacity is obtained. It can be seen from the figure that for the LNCM-811 positive electrode material, the capacity increases significantly with the increase of the coating thickness at first, and the capacity is highest when the coating thickness reaches 10-20nm; then as the coating thickness continues to increase, the capacity slowly decreases; when the coating thickness is greater than 40nm, the capacity gradually decreases but the change value is relatively small; by fitting the relationship curve, the following formula is obtained: 1) When 0nm<d≤40nm, C estimated value = 188+4d-0.15d 2 +0.0016d 3 ; 2) When d>40nm, C estimated value = 210 / (d-40) 0.007 , where C is the estimated value of the first discharge specific capacity of the button battery, in mAh / g; d is the thickness of the coating layer in the coated active material, in nm.

[0148] (2) Differential Scanning Calorimetry (DSC) Test:

[0149] According to the button cell preparation method in Test (1), the active materials finally provided in Example 1 and Comparative Examples 1-2 were used as positive electrode active materials to prepare button cells.

[0150] Test conditions: Charge button cells at 0.1C constant current and constant voltage in the voltage range of 3.0-4.3V until they are fully charged. Then disassemble the cells and perform DSC test on the positive electrode.

[0151] Figure 3 The DSC test curves of Example 1, Comparative Example 1 and Comparative Example 2 are shown. It can be seen from the figure that the peak temperature of Example 1 is higher, the peak intensity is weaker, and the heat release is relatively small, that is, the coated active material obtained in Example 1 is safer; on the contrary, the initial peak and peak temperature of Comparative Example 1 are lower; the peak intensity and peak area of ​​Comparative Example 2 are larger, and the heat release is significantly increased, which indicates that the materials provided by Comparative Examples 1 and 2 have greater safety hazards. In summary, the coating using electrospinning technology in Example 1 of the present invention is conducive to improving safety performance.

[0152] (3) First discharge specific capacity and first efficiency test:

[0153] According to the button cell preparation method in Test (1), the active materials finally provided in Examples 1-9 and Comparative Examples 1-5 were used as positive electrode active materials to prepare button cells respectively.

[0154] Test conditions: Different voltage ranges were set according to the specific materials of each embodiment and comparative example, and the button cell was charged at 0.2C constant current and constant voltage, and then discharged at 0.2C constant current to obtain the first discharge specific capacity and first efficiency.

[0155] The voltage range of the test and the measured first discharge specific capacity and first efficiency results are shown in Table 1, where the measured first discharge specific capacity is the actual first discharge specific capacity of the active material after coating, recorded as C test value.

[0156] The estimated first discharge specific capacities (i.e., estimated C values) of Examples 1-9 are summarized in Table 1, where:

[0157] Estimated value through C = 188 + 4d - 0.15d 2 +0.0016d 3 The estimated first discharge specific capacities of the coated active materials of Example 1 and Examples 5-8 were calculated.

[0158] Estimated value through C = 150 + 4d - 0.15d 2 +0.0016d 3 The estimated first discharge specific capacity of the coated active material of Example 2 was calculated.

[0159] Estimated value through C = 90 + 4d - 0.15d 2 +0.0016d 3 The estimated first discharge specific capacity of the coated active material of Example 3 was calculated.

[0160] Estimated value through C = 115 + 4d - 0.15d 2 +0.0016d 3 The estimated first discharge specific capacity of the coated active material of Example 4 was calculated.

[0161] Estimated value through C = 210 / (d-40) 0.007 The estimated first discharge specific capacity of the coated active material of Example 9 was calculated.

[0162] (4) Cyclic performance test:

[0163] According to the button cell preparation method in Test (1), the active materials finally provided in Example 1 and Comparative Examples 1-2 were used as positive electrode active materials to prepare button cells.

[0164] Test conditions: At 25°C, in the voltage range of 3.0-4.4V, the button cell was charged at 1C constant current and constant voltage, and then discharged at 1C constant current, for a total of 51 cycles.

[0165] Figure 4The cycle curves of Example 1, Comparative Example 1 and Comparative Example 2 are shown, that is, the capacity retention rate of Example 1, Comparative Example 1 and Comparative Example 2 varies with the number of cycles. It can be seen from the figure that compared with the uncoated LNCM-811 material provided in Comparative Example 1, the capacity retention rate corresponding to LiNbO3 coated on the surface of LNCM-811 in Example 1 and Comparative Example 2 is higher, that is, the cycle performance can be improved by coating, but the improvement in cycle performance varies with different coating methods. Example 1 of the present invention is coated using electrospinning technology, and Comparative Example 2 is coated using a fire method. It can be clearly seen from the figure that the capacity retention rate of Example 1 is higher than that of Comparative Example 2, that is, Example 1 of the present invention is coated using electrospinning technology, which is beneficial to improving the cycle performance.

[0166] Table 1

[0167]

[0168] analyze:

[0169] It can be seen from Examples 1-4 and Example 9 in the above table that the present invention utilizes electrospinning technology and sintering process to coat a thin and uniform coating layer on the surface of the active material. After testing the prepared coated active material, it was found that the coated active material exhibited a high first discharge specific capacity test value and a high first efficiency.

[0170] It can be seen from Example 1 and Examples 5-6 that when the air pressure of the airflow in step (3) is relatively small or relatively large, it will lead to an uneven coating layer, thereby resulting in a decrease in capacity.

[0171] It can be seen from Examples 1-9 that the error between the estimated C value calculated by the relationship and the measured C test value is relatively small.

[0172] It can be seen from Example 1 and Examples 7-8 that if the sintering temperature in step (4) is too low, the polymer in the coating layer cannot be completely removed, resulting in increased resistance and reduced capacity; if the sintering temperature in step (4) is too high, the coating layer will enter the structural phase, hindering the transport of lithium ions and resulting in reduced capacity.

[0173] It can be seen from Examples 1-4, Comparative Example 1 and Comparative Examples 3-5 that if LNCM-811, lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate positive electrode materials are not coated, the capacity and first efficiency will be reduced.

[0174] It can be seen from Example 1 and Comparative Example 2 that when the ternary cathode material LNCM-811 is pyro-coated with LiNbO3, the capacity and first efficiency are low. The results show that compared with the traditional pyro-coating, the present invention uses electrostatic spinning technology for coating, which is beneficial to the capacity and improves the first efficiency.

[0175] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A coated active material prepared by electrospinning technology, characterized in that: The coated active material comprises an active material core and a coating layer coated on the surface of the active material core; The coated active material meets the following conditions: When 0nm<d≤40nm, estimated value of C = C0+4d-0.15d 2 +0.0016d 3 ; When d>40nm, C estimated value = C1 / (d-40) 0.007 ; Wherein, the estimated value of C is the estimated value of the first discharge specific capacity of the coated active material, in units of mAh / g; C0 is a constant, ranging from 90 to 190; C1 is a constant, ranging from 110 to 210; d is the thickness of the coating layer, in nm.

2. The coated active material according to claim 1, characterized in that: The first discharge capacity test value of the coated active material is recorded as C test value, and the absolute value of the difference between the C estimated value and the C test value is ≤5 mAh / g; The coating layer has a thickness of 2-100 nm.

3. A method for coating active materials using electrospinning technology, characterized in that: The method comprises: (1) mixing a coating agent, a polymer and a solvent to obtain a dispersion; (2) Using the dispersion as a spinning solution and placing the active material in a flowing state, electrospinning is performed to form a coating precursor layer on the surface of the active material, followed by sintering to obtain the coated active material according to claim 1 or 2.

4. The method according to claim 3, characterized in that The coating element in the coating agent includes at least one of W, Al, La, Zr, Ti, N, B, Si, P, Sr, Y, Nb, Mo or Ce elements; and / or, based on the total mass of the dispersion as 100%, the mass fraction of the coating element in the coating agent is 0.1-70%; And / or, based on the total mass of the dispersion being 100%, the mass fraction of the polymer is 5-70%.

5. The method according to claim 3, characterized in that: The solvent includes a first solvent and a second solvent; the first solvent and the second solvent independently include at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone or ethanol; And / or, the mixing in step (1) is step-by-step mixing, and the step-by-step mixing includes the following steps: (i) a polymer and a first solvent are first mixed to obtain a spinning solution A; a coating agent and a second solvent are second mixed to obtain a spinning solution B; (ii) performing a third mixing of the spinning solution A and the spinning solution B to obtain the dispersion; And / or, the temperature of the second mixing is 50-150° C., and the time is 1-48 hours.

6. The method according to claim 3, characterized in that In step (2), the active material is placed in a flowing state by means of air flow; And / or, the air pressure of the air flow is 0.01-2.00 MPa; and / or, the temperature of the airflow is 20-30°C; And / or, the gas in the airflow is dry gas, and the dew point of the dry gas is ≤-10°C.

7. The method according to claim 3, characterized in that In step (2), electrospinning is performed using an electrospinning device; The electrospinning device comprises a spinning chamber; a liquid supply component and a receiving component are arranged in the spinning chamber, the liquid supply component comprises a propeller, a syringe for containing spinning liquid and an injection needle connected to the syringe, the propeller is used to control the propulsion speed of the syringe, the injection needle is arranged opposite to the receiving component; the injection needle and the receiving component are externally connected to a high-voltage power supply; A permeable cap is disposed on the top of the spinning chamber; an air inlet is disposed on the bottom of the spinning chamber for introducing air flow into the spinning chamber so that the active material flows in the area between the injection needle and the receiving component.

8. The method according to claim 3, characterized in that The electrospinning time is 1-600 min.

9. The method according to claim 3, characterized in that: The sintering temperature in step (2) is 200-500°C; And / or, the sintering time is 2-10 hours.

10. A secondary battery, characterized in that: The electrode of the secondary battery comprises the coated active material according to claim 1 or 2, or the coated active material prepared by the method according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Positive active material, preparation method thereof and electrochemical energy storage device

    CN110957474A

  • Ternary positive electrode material doped, coated and modified by fast ion conductor and preparation method of material

    CN112599756A